2012
DOI: 10.1371/journal.pbio.1001283
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptically Localized Cyclic GMP-Dependent Protein Kinase 1 Is a Key Determinant of Spinal Synaptic Potentiation and Pain Hypersensitivity

Abstract: Electrophysiological and behavioral experiments in mice reveal that a cGMP-dependent kinase amplifies neurotransmitter release from peripheral pain sensors, potentiates spinal synapses, and leads to exaggerated pain.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
107
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 50 publications
5
107
0
Order By: Relevance
“…Consistent with our observations with NO blockade (above), we observed that mice lacking Prkg1 , a key target of the NO-cGMP pathway, specifically in peripheral nociceptors (Luo et al., 2012), did not develop mechanical and thermal hypersensitivity with VEGF-A (Figure 3E). We also found several lines of evidence linking VEGF-A signaling to modulation of TRPV1, the key final effector of thermal hyperalgesia (Basbaum et al., 2009).…”
Section: Resultssupporting
confidence: 92%
“…Consistent with our observations with NO blockade (above), we observed that mice lacking Prkg1 , a key target of the NO-cGMP pathway, specifically in peripheral nociceptors (Luo et al., 2012), did not develop mechanical and thermal hypersensitivity with VEGF-A (Figure 3E). We also found several lines of evidence linking VEGF-A signaling to modulation of TRPV1, the key final effector of thermal hyperalgesia (Basbaum et al., 2009).…”
Section: Resultssupporting
confidence: 92%
“…In primary sensory neurons of the dorsal root ganglia, cGKI also mediates potentiation of IP3R activity through phosphorylation of the receptor, leading to increased Ca 2+ release from the ER, which is functionally linked to synaptic LTP (43). IP3R-associated cGK substrate (IRAG) is required for cGKI-mediated phosphorylation of IP3Rs (44).…”
Section: Discussionmentioning
confidence: 99%
“…(Hirasawa et al 2007; Hirota et al 2003) Importantly, phospholipid signaling has recently been implicated in the regulation of nociception,(Neely et al 2012) consistent with the potential importance of this candidate gene in pain perception associated with its regulation of ITPR1. (Komalavilas and Lincoln 1994; Luo et al 2012; Wagner et al 2003)…”
mentioning
confidence: 99%